The Influence Of Perceived Transformational Leadership Style And Job Satisfaction On Organizational Commitment In Teacher - Previarzya, Realita Sereen; Thamrin, Winny Puspasari (MOTIVA: JURNAL PSIKOLOGI, 2024)
Teachers play an important role in the success and sustainability of the organization. Thus, teachers are required to have a work attitude that plays an active role in achieving school goals and a high commitment to school organizations. Commitment to the organization is an attitude that describes an individual's orientation to the organization as indicated by loyalty, self-identification and involvement in the goals of the organization. Transformational leadership and job satisfaction are predicted to have a role in influencing organizational commitment to teachers. This study aims to empirically prove the effect of transformational leadership style and job satisfaction on organizational commitment in teachers. The research sample was 238 high school teachers in Bogor Regency. The data analysis technique in this study used multiple linear regression analysis. The results of this study show that transformational leadership and job satisfaction have a 55.7% influence on organizational commitment with a significance level of p=0.000. This shows that transformational leadership and job satisfaction have a very significant influence on organizational commitment. The results of this study also show that organizational commitment, perceived of transformational leadership style, and job satisfaction among high school teachers in Bogor Regency are in the high category.